Strain assisted ultrafast spin switching on Co2@C60 endohedral fullerenes. (June 2015) - Li, Chun; Liu, Jing; Zhang, Shaobin; Lefkidis, Georgios; Hübner, Wolfgang
Abstract: The ultrafast spin switching on double-magnetic-center endohedral fullerenes Co2 @C60 under uniaxial tensile strain is investigated through ab initio calculations. The applied strain along the Co–Co bond plays an important role in the spin density distribution, especially for the low-lying magnetic states, and thus dominates the spin-switching processes. It is shown that the achieved local spin switching on one of the Co atoms via the Λ process depends not only on the configuration symmetry of the system but also on the magnitude of the applied tensile strain. The fastest spin switching scenario is found in the Co2 off-center case. The strain-induced spin density redistribution and strain modulation of spin switching provide the possibility to control the spin degree of freedom using a mechanical effect, which could lead to promising applications in the design of integrated spin-logic devices.